下顎頭に生じた周辺性骨腫の1例 - 櫻井, 博理; 石川, 恵生; 橘, 寛彦; 尾崎, 尚; 飯野, 光喜; 遊佐, 和之 (日本口腔外科学会雑誌, 2014)
Osteoma is a benign tumor comprising mature bone tissue. It is classified as peripheral, central, or extraskeletal. Peripheral osteoma of the mandibular condyle is a rare entity. We report a case of peripheral osteoma arising in the left mandibular condyle. A 31-year-old man presented with progressive deviation of the chin and malocclusion. He was in good health with no history of facial trauma. After some examinations were performed, a clinical diagnosis of a benign bone tumor in the left mandibular condyle was made. A condylectomy was performed, and the postoperative course was uneventful. The histological diagnosis was peripheral osteoma. Four years after the operation, the occlusion and facial asymmetry remain substantially improved. No recurrence has occurred. This article includes a review of previously reported cases.